KIRCHHOFF PRE-STACK DEPTH MIGRATION ON COMPLEX STRUCTURES - Mohd Nasir, Asyraf (2016)
The fundamental of the thesis is to improve the synthetic seismic data using a migration technique. The author decided to obtain the model the synthetic seismic using Forward Modelling and then, test the ability of Pre-Stack Depth Migration in improving the data quality for complex subsurface structures. This study first model the synthetic seismic gather using 2D acoustic forward modelling on the velocity model constructed based on the Hess VTI Benchmark model. Then, the author began the flow of the migration job that consists of travel time computation and then, Kirchhoff Pre-Stack Depth migration on the synthetic dataset. Once the synthetic gather data was ready, the author manipulates the migration aperture to observe which aperture number that suits the model best. The results of the study are expected to be of help in improving the seismic gather that has similar complex subsurface structure but further studies could further take another step toward betterment. The author recommends a seismic attribute study when interpreting subsurface structures on top of the Imaging processing done as well as anisotropic migrations to address heterogenous media.